Identification of a satellite fatty acid ethyl ester synthase from human myocardium as a glutathione S-transferase. - Bora, P S (1989)
Nonoxidative alcohol metabolism catalyzed by fatty acid ethyl ester (FAEE) synthases may contribute to extrahepatic injury resulting from alcohol abuse. Unlike rabbit myocardial FAEE synthase, that from human heart has a satellite minor synthase (I) eluting from DEAE cellulose at a conductivity of 5 mS. Synthase I was purified 1,118-fold to homogeneity by sequential gel permeation, hydrophobic interaction, and Superose-12 fast-protein liquid chromatographies. SDS-PAGE showed a single polypeptide with a molecular mass of 26 kD and gel permeation chromatography indicated a molecular mass of 52 kD for the active enzyme. Homogeneous synthase I catalyzed ethyl ester synthesis at highest rates with unsaturated octadecanoic fatty acid substrates. The amino acid composition of synthase I was highly homologous to that of human myocardial major synthase, recently identified as an acidic glutathione (GSH) S-transferase. Antibody raised against homogeneous human heart major synthase cross-reacted with the 26-kD synthase I. FAEE synthase co-chromatographed with GSH S-transferase on DEAE cellulose, Sephadex G-100 and S-hexylglutathione agarose, and also displayed GSH S-transferase activity in catalyzing the conjugation of GSH with nitrobenzene-containing carcinogens. Thus, human myocardium contains a satellite peak of FAEE synthase activity and it is a neutral GSH S-transferase.